The thyroid hormone system disrupting potential of resorcinol in fish - Imke Van Dingenen; Emma Andersen; Sina Volz; Monica Christiansen; Jiří Novák; Ann-Cathrin Haigis; Emma Stacy; Brett R. Blackwell; Daniel L. Villeneuve; Lucia Vergauwen; Klára Hilscherová; Henrik Holbech; et al. (Ecotoxicology and Environmental Safety)
Environmental pollutants capable of interfering with the thyroid hormone (TH) system increasingly raise concern for both human and environmental health. Recently, resorcinol has received attention as a compound of concern due to its endocrine disrupting properties. It is a known inhibitor of thyroperoxidase (TPO), an enzyme required in TH synthesis, and therapeutic use of resorcinol exposure has led to hypothyroidism in humans. There is limited evidence concerning ecotoxicologically relevant effects of resorcinol in fish. A set of adverse outcome pathways (AOPs) has recently been developed linking thyroid hormone system disruption (THSD) to impaired swim bladder inflation and eye development in fish. In the present study, these AOPs were used to provide the background for testing potential THSD effects of resorcinol in zebrafish eleutheroembryos. We exposed zebrafish eleutheroembryos to resorcinol and assessed TH levels, swim bladder inflation and eye morphology. As a TPO inhibitor, resorcinol is expected to affect TH levels and eye morphology but not swim bladder inflation during embryonic development. Indeed, thyroxine (T4) levels were significantly decreased following resorcinol exposure. In contrast to our hypothesis, swim bladder inflation was impaired at 5 days post fertilization (dpf) and no effects on eye morphology were detected. Therefore, in vitro assays were performed to identify potential additional thyroid hormone system disruption-related mechanisms through which resorcinol may act. Two new mechanisms were identified: TH receptor (TR) antagonism and transthyretin (TTR) binding inhibition. Both of these mechanisms can plausibly be linked to impaired swim bladder inflation and could, therefore, explain the observed effect. Overall, our study contributes to the knowledge of the THSD potential of resorcinol both in vivo in the zebrafish model as well as in vitro.